Pemilihan Kepala Daerah Oleh Dewan Perwakilan Rakyat Daerah Ditinjau Dari Pasal 18 Ayat 4 Undang-Undang Dasar 1945 - Pery Rehendra Sucipta; M Riski Ansori (Journal of Judicial Review, 2016)
Indonesia is a democratic country according to Article 1 paragraph 2 of the Constitution of 1945. The setting of the election of heads of state institutions as well as at the local level provides clear evidence that 1945 is the Constitution as the basic law is written very democratic, especially in terms of the local elections with an electoral system that is also undergoing some changes of direct election by the people and the election through a representative, namely by the Regional representatives Council (DPRD). However, in the 2014 election by Parliament will again apply with the enactment of Law No. 22 of 2014 On the Election of governors, regents and mayor. But then the law reap a lot of resistance among the public because it is undemocratic and then canceled by the President. Based on this, we propose two (2) formulation of the problem addressed in this study: first, How Does the local elections based on Law Number 22 Year 2014 On the Election of governors, regents and mayors through parliament a second, Do the selection mechanism of the Regional Head made by parliament in accordance with article 18 paragraph 4 of the 1945 Constitution.This study uses a conceptual foundation, juridical and theory. Juridical basis in the form of Act No. 22 of 2014 On the Election of governors, regents and mayors. Then, the theoretical basis in adoption is the Constitutional Theory, Stufenbau Theory, Theory of Democracy and the Theory of Trias Politica. This study uses normative legal research. Therefore, methods of data analysis in this study is called qualitative descriptive.Based on this research, the mechanism of election of heads of regions based on Law Number 22 Year 2014 concerning the local elections through the Parliament set out in articles 6 to 33 organized by the Committee of Voters of members of parliament and elections are held in the plenary session of Parliament that issue the voting rights in a manner stand up. Regional Head Election Judging by Parliament Pursuant to Article 18 Paragraph 4 of the Constitution of 1945 and linked to the local elections in accordance Theory Constitutional Law, Theory of Hans Kelsen, Democracy and Trias Politica local elections by Parliament in accordance with the principles of democracy because it is not contrary to Law 194.